Redescription of Physaloptera Liophis Vicente & Santos, 1974 (nematoda: Physalopteridae) a parasites of anura from pampa bioma, Brazil - A. Coimbra, Marco Antonio (2024)
Physaloptera liophis Vicente & Santos, 1974 was described as parasite of snake in southeastern Brazil; however, some morphological aspects need updating. In the study of helminths associated with Rhinella dorbignyi (Duméril & Bibron, 1841) (Anura: Bufonidae) in the south of the country, specimens of P. liophis were found and used for the redescription presented by this paper. Thirteen out of 100 anurans under analysis were parasitized by P. liophis. Redescription provides new information on the number of papillae of males and on morphological characteristics of the reproductive system of females.